Synergistic Impact of Dual Hereditary Protein C and S Deficiency Exacerbated by Acute Pan-Sinusitis in Recurrent Cerebral Venous Sinus Thrombosis: A Case Report - Nyoman Angga Santosa; Ni Made Renny Anggreni Rena (HM Publisher, 2026)
Cerebral venous sinus thrombosis is a rare neurovascular emergency characterized by thrombotic occlusion of the dural venous sinuses. While various prothrombotic states predispose individuals to this condition, the concurrent presentation of dual hereditary Protein C and Protein S deficiency is exceptionally uncommon. This dual coagulopathy severely impairs natural anticoagulant mechanisms. We report the case of a 49-year-old male presenting with severe postural dizziness, vertigo, and bilateral lower extremity paresthesia. The patient had a history of a previous cerebral venous sinus thrombosis diagnosed in September 2023, for which he was receiving warfarin. Due to historically variable international normalized ratio levels and new symptoms, a comprehensive re-evaluation was initiated. Neuroimaging confirmed acute extension of the thrombosis involving the superior sagittal, left transverse, and left sigmoid sinuses, alongside an incidental finding of acute pan-sinusitis. To eliminate the confounding effect of warfarin on thrombophilia screening, the patient was bridged to low-molecular-weight heparin for fourteen days prior to testing. Subsequent functional assays confirmed profound deficiencies in Protein C (26 IU/dL) and Protein S (13 IU/dL). Management involved treating the regional pan-sinusitis and a strategic pharmacological transition to rivaroxaban (20 mg daily), resulting in complete clinical stabilization. In conclusion, this case underscores the necessity of rigorous methodological timing in thrombophilia testing and highlights regional inflammation as a potent acute trigger in genetically susceptible individuals. It further demonstrates the long-term viability of direct oral anticoagulants in complex dual inherited coagulopathies.